2016
DOI: 10.1021/acsami.6b04073
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Role of Co in Improving the High-Rate Capability and Cycling Performance of Layered Na0.7Mn0.7Ni0.3–xCoxO2 Cathode Materials for Sodium-Ion Batteries

Abstract: Co substitution has been extensively used to improve the electrochemical performances of cathode materials for sodium-ion batteries (SIBs), but the role of Co has not been well understood. Herein, we have comprehensively investigated the effects of Co substitution for Ni on the structure and electrochemical performances of Na0.7Mn0.7Ni0.3-xCoxO2 (x = 0, 0.1, 0.3) as cathode materials for SIBs. In comparison with the Co-free sample, the high-rate capability and cycle performance have been greatly improved by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 70 publications
3
115
1
Order By: Relevance
“…By comparing with the spectra of the standard transition metal oxide compounds, it is revealed that the average valence states of the Co, Mn, and Ti ions in the as‐synthesized NCMT‐2 are 2+, 3.7+, and 4+. It is very surprising that Co ions can be stabilized at 2+ in the P2‐type layer‐structured compounds, since the valence state of Co ions in most layer‐structured cathode materials is 3+ 12, 23, 39. In addition, the valence state of Mn ions in NCMT‐2 is 3.7+, which is higher than Mn 3+ in tunnel‐structured Na 0.66 Mn 0.66 Ti 0.34 O 2 18.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…By comparing with the spectra of the standard transition metal oxide compounds, it is revealed that the average valence states of the Co, Mn, and Ti ions in the as‐synthesized NCMT‐2 are 2+, 3.7+, and 4+. It is very surprising that Co ions can be stabilized at 2+ in the P2‐type layer‐structured compounds, since the valence state of Co ions in most layer‐structured cathode materials is 3+ 12, 23, 39. In addition, the valence state of Mn ions in NCMT‐2 is 3.7+, which is higher than Mn 3+ in tunnel‐structured Na 0.66 Mn 0.66 Ti 0.34 O 2 18.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the valence state of Mn ions in NCMT‐2 is 3.7+, which is higher than Mn 3+ in tunnel‐structured Na 0.66 Mn 0.66 Ti 0.34 O 2 18. It is well known that high‐spin Mn 3+ with the electron configuration of (t 2g ) 3 (e g ) 1 in the 3D orbital exhibits very strong Jahn–Teller distortion due to the single occupancy of a degenerate e g orbital 12, 22. The low valence Co 2+ substitution in NCMT‐2 introduces more Mn 4+ because the required charge balance, which resulted the average Mn 3.7+ in the P2‐type structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations